Pembuatan Rencana Strategis SI/TI Sebagai Acuan Pengembangan SI/TI Rumah Sakit Pelabuhan Palembang - Netti Herawati; Dedy Syamsuar; Yesi Novaria Kunang (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
The Palembang Port Hospital has used and utilized IT tools in line with the vision of becoming the best hospital in the national health industry with world-class professional services. To benefit from the use of IT equipment, the management of the Palembang Port Hospital must have knowledge of how the device is planned properly so that the results obtained are as expected. Otherwise it will cause a mismatch between the current device / application and the application needed in the future. Based on this, a strategic planning is required so that IT development runs directed and in accordance with the expected values ​​of hospital management. The preparation of this strategic plan uses the Anita Cassidy framework in 4 phases, namely (1) Visioning Phase discusses current business conditions, (2) Analysis Phase discusses current IT conditions, (3) Direction Phase contains IT planning stages and (4) Recommendation Phase is the final result of the preparation of a strategic plan in the form of a final roadmap. In the preparation of the strategic plan for the Palembang Port Hospital, 9 projects were identified, namely 3 projects related to applications, 4 projects related to network infrastructure development, 2 documentation projects and IT training. In addition, an estimate of the time the project will start is also developed.